Compressive Strength Of Mortar Mixing Sea Sand With Portland Cement Composite (PCC) - Adnan Adnan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Indonesia is an area rich in sea sand. The aim of this research is to determine the comparison of the compressive strength of mortar derived from sea sand and river sand, as well as the feasibility of using sea sand as a material in construction in coastal areas. The results of the research showed that the compressive strength of the mortar from the two materials tested at 28 days had a difference in compressive strength of up to 37.45%, the mortar made from sea sand aggregate produced a mortar compressive strength of 14.13 Mpa which can be categorized as type S mortar with minimum value 12.5 MPa, meanwhile, mortar made from fine river sand aggregate produces a mortar compressive strength of 22.59 MPa and is included in the type M mortar category which has a minimum value of 17.2 Mpa.